Limited mass-independent individual variation in resting metabolic rate in a wild population of snow voles (Chionomys nivalis) - Hagmayer, Andres; Camenisch, Glauco; Canale, Cindy; Postma, Erik; Bonnet, Timothée (Dryad, 2020)
Resting metabolic rate (RMR) is a potentially important axis of
physiological adaptation to the thermal environment. However, our
understanding of the causes and consequences of individual variation in
RMR in the wild is hampered by a lack of data, as well as analytical
challenges. RMR measurements in the wild are generally characterized by
large measurement errors and a strong dependency on mass. The latter is
problematic when assessing the ability of RMR to evolve independently of
mass. Mixed models provide a powerful and flexible tool to tackle these
challenges, but they have rarely been used to estimate repeatability of
mass-independent RMR from field data. We used respirometry to obtain
repeated measurements of RMR in a long-term study population of snow voles
(Chionomys nivalis) inhabiting an environment subject to large circadian
and seasonal fluctuations in temperature. Using both uni- and bivariate
mixed models, we quantify individual repeatability in RMR and decompose
repeatability into mass-dependent and mass-independent components, while
accounting for measurement error. RMR varies among individuals, i.e. is
repeatable (R=0.46), and strongly co-varies with BM. Indeed, much of the
repeatability of RMR is attributable to individual variation in BM, and
the repeatability of mass-independent RMR is reduced by 41% to R=0.27.
These empirical results suggest that the evolutionary potential of RMR
independent of mass may be severely constrained. This study illustrates
how to leverage bivariate mixed models to model field data for metabolic
traits, correct for measurement error, and decompose the relative
importance of mass-dependent and mass-independent physiological variation.
Keywords: Chionomys nivalis; snow voles